QuickBite: A Cutting-edge Food Ordering System Developed with Flutter - Eisa, Abobakr; Hasan, Abd Samad (Applied Information Technology And Computer Science, 2025)
Mobile applications have become a pivotal strategy for customer retention, especially with the prevalence of smartphones and improved wireless networks. Traditional restaurant ordering methods often lead to inefficiencies and dissatisfaction, highlighting the need for a comprehensive mobile food ordering platform. This project aims to develop such a platform to address issues like long wait times, order inaccuracies, and poor order visibility. The waterfall model is used to create this application, ensuring a structured development process. The application, to be deployed in Sudan where no similar app exists, will be available for both Android and iOS users. Testing has shown it effectively connects customers with restaurants in just a few steps. Expected outcomes include enhanced meal ordering convenience, flexible payment methods, and an improved user experience with a user-friendly interface. Users can also apply discount coupons and designate favorite items for quick access, making the ordering process more efficient and enjoyable.